Nevidna povezava ugleda države in podjetij - Jančič, Zlatko (Teorija in praksa, 1998)
The article deals with the phenomenon of country's image and its influence on the images of domestic companies. It is stated that image, reputation and identities are invisibly implied in the people's, organizations' as well as countries' behavior. In order to understand the interdependence of country's and companies' reputation, it is important to take into account the concepts of the state's and company's origin, since they offer the answers regarding the successfulness in international exchange. Finally, we analyze the neutral or endorsed image of Slovenia, being a young country in transition. We pose the question whether such image leads us towards the poverty chain or towards the wealth chain.
Keywords: corporation; podjetje; država; state; identiteta; tržno komuniciranje; strategija; Slovenia; Slovenija